Managing distribution channel for beer products in habeco trading one member company limited = đẩy mạnh quản lý kênh phân phối các sản phẩm Bia Hà Nội tại Công ty TNHH MTV thương mại HABECO - Nguyễn, Mạnh Hùng (Khoa Quản trị kinh doanh, 2018)
CHAPTER 1: INTRODUCTION. CHAPTER 2: THEORETICAL BACKGROUND ON DISTRIBUTION CHANNEL MANAGEMENT FOR BEER INDUSTRY. CHAPTER 3: LITERATURE REVIEW. CHAPTER 4: CURRENT SITUATION OF DISTRIBUTION CHANNEL MANAGEMENT FOR BEER PRODUCTS OF HABECO TRADING ONE MEMBER COMPANY LIMITED. CHAPTER 5: SOLUTIONS TO STRENGTHEN DISTRIBUTION CHANNEL MANAGEMENT AT HABECO TRADING ONE MEMBER CO., LTD